Lessons from a research partnership in southwest England to understand community palliative care needs in rural, coastal and low-income communities - Lorraine Hansford; Katrina Wyatt; Siobhan Creanor; Sheena McCready; Richard Harding (NIHR Journals Library, 2024)
Background The South West Peninsula (Cornwall, Devon, Somerset) has the highest proportion of over 65s (24.2%) and is the only English rural population with greater economic deprivation than in urban areas. Coastal populations have the worst health outcomes in England. Despite innovation among communities to support those with health and care needs in later life, recruitment to palliative care research in the region is low and there has been no evaluation of public health palliative care interventions. Objectives A new South West Peninsula Palliative Care Research Partnership was funded for 15 months, bringing together four universities, the voluntary and community sector (including hospices) and local National Institute for Health and Care Research networks. The aim was to establish a sustainable multisectoral partnership that would identify community-based support needs for underserved rural and coastal populations by: conducting a literature scoping review on interventions to enable community members to support the dying; delivering a research capacity-building programme; co-creating public and patient involvement capacity; determining the resources and needs for communities to support dying well; integrating findings to develop a framework of community-based support and identify future research questions; establishing a sustainable research network infrastructure for the long-term design and delivery of palliative care research. Design We convened partners to identify research needs and co-designed activities to meet our objectives. These included a scoping review; a capacity-building programme of training, seminars and a journal club; forming a patient and public involvement group; a multistranded community engagement programme using different creative approaches; four focus groups with members of the public and one with community workers; and producing three 'storytelling' audio recordings. Findings were presented to the partnership at a regional workshop. Results The scoping review showed that community-engaged palliative care interventions can improve outcomes for individuals but provided little evidence about which approaches work for different communities. Five online seminars and a quarterly journal club to develop research capacity were regularly attended by 15 to 25 participants from across the partnership. While evaluating our engagement methods was beyond the partnership's scope, levels of participation suggested that creative methods of engagement show potential to help researchers and practitioners better understand the needs and priorities of underserved populations. Data showed that rural, coastal and low-income communities face challenges in accessing end-of-life care and support due to issues such as transport to and distance from services, erosion of neighbourhood networks, isolation from family and friends, 'patchiness' of palliative care services and a lack of care providers. Community organisations are well-placed to co-produce and facilitate methodologies for involving communities in palliative care research. Limitations Although activities took place in diverse areas, it was not possible within the available resources to cover the entire large geographical region, particularly the most isolated rural areas. Conclusions Partnerships bringing together voluntary and community sector organisations, palliative care providers, health and social care providers, individuals with experience and academics have potential to design future research and public health interventions that better understand local context, involving and supporting communities to address their needs at end of life. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme as award number NIHR135312. Plain language summary What did we want to improve? England's South West Peninsula (Cornwall, Devon, Somerset) has high levels of poverty and an ageing population. There are some community groups which enable individuals to support each other at the end of life. However there has been little local palliative (i.e. end-of-life) care research to understand people's needs in rural and coastal areas. What did we do? We created the South West Peninsula Palliative Care Research Partnership including four universities, voluntary and community organisations (including hospices), health research agencies, and a group of individuals interested in palliative care. We wanted to build a sustainable partnership that would identify what communities need to support each other at end of life and help individuals and organisations to plan and participate in research. We reviewed existing research evidence and ran a programme of training events and community activities (an interactive display, focus groups, one-to-one conversations and 'storytelling'). Finally, we came together to discuss the findings and plan next steps. What did we find? Getting support at the end of life can be difficult in the region because of poor transport, distance from services, isolation from support networks, and patchy palliative and social care services. We found that using creative ways to involve people, like the interactive display, helped clinicians and researchers better understand local needs. Our experience of partnership working showed that palliative care organisations, academics and community organisations working alongside each other can help services reach these areas, and make it easier for people to be involved in research. What does this mean? We hope that continuing this partnership will help communities share and develop expertise in supporting patients and families with palliative care needs, and help clinical services and universities involve people in rural, coastal and low-income areas in planning, delivering and participating in research that addresses their priorities.